Physical and Numerical Modelling of Mooring Forces and Displacements of a Wave Activated Body Energy Converter - Elisa Angelelli; Francesco Ferri; ZANUTTIGH, BARBARA; MARTINELLI, LUCA (Volume 9A: Ocean Renewable Energy, 2014)
The paper analyses the forces on the mooring system and the device motions of a floating Wave Activated Body Energy Converter under ordinary and extreme wave conditions. The investigation has been carried out with physical and numerical approaches. The physical tests were performed in 1:60 scale in the shallow-water wave tank of Aalborg University, whereas the numerical simulations were performed in 1:1 scale with the AQWA code developed by ANSYS. The spread mooring system tested in the laboratory allowed for an efficient device keeping while minimising the space. The loads on the moorings increase with increasing the significant wave height and show a modest trend with the peak wave length. These experimental measurements were compared with the numerical results, suggesting that AQWA model is able to accurately reproduce the standard deviation of the forces on the mooring lines. From the simulations it is highlighted that the device should work far from resonance condition, because when the typical wave period is near to the natural period (in surge) the forces acting on the mooring lines increase, resulting in a high level of energy loss.